Pengetahuan Ibu Hamil Trimester III Tentang KB Pasca Persalinan di Puskesmas Jetis Kota, Yogyakarta - Nining Kurnia; Yhona Paratmanitya; Oktaviana Maharani (Alma Ata University Press, 2015)
The population of Indonesia increased every year. The goverment makes family planning post delivery to press off Indonesian growth. In Yogyakarta family planning post delivery were used by 527 people, at Puskesmas Jetis were 167 women from 363 total target of pregnant women. A succession of this program influenced by knowledge and education. The purpose of this study was to know the knowledge level of pregnant women in trimester III about family planning post delivery at Puskesmas Jetis Yogyakarta. The methode of this study was descriptive quantitative with cross sectional design. The sample obtained by saturated sampling technique which consisted of 45 pregnant women trimester III. The data used univariate analysys. The results showed that most of pregnants women in trimester III was aged 20-35 years (77.7%), high school education (37.8%), and there was 51.1% of pregnant women in fair knowledge level. Most of pregnant women decides to used family planning injection post delivery (44.4%). In conclusion, the knowledge level of pregnant women in trimester III about family planning post delivery was mostly in fair knowledge level.